2015
DOI: 10.15241/prm.5.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Development of Counseling Students’ Self-Efficacy During Preparation and Training

Abstract: A purposeful sample of 359 graduate counseling students completed a survey assessing factors influencing program enrollment decisions with particular attention to students' awareness of and importance ascribed to accreditation from the Council for Accreditation of Counseling and Related Educational Programs (CACREP) prior to and following enrollment. Results indicated that accreditation was the second most influential factor in one half of the students' enrollment decisions; nearly half of participants were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 38 publications
6
37
2
5
Order By: Relevance
“…Meyer () reported that master’s‐level students in a rehabilitation counseling program had an increase in their CSE during the counseling skill training course. Mullen, Uwamahoro, Blount, and Lambie () found that master’s‐level counseling students’ CSE increased over time as they progressed through the preparation program. However, although there are several studies that explored the development of students’ CSE, few studies exist to investigate a longitudinal change in students’ CSE throughout their preparation programs (e.g., from orientation to graduation from the program).…”
Section: Csementioning
confidence: 99%
See 1 more Smart Citation
“…Meyer () reported that master’s‐level students in a rehabilitation counseling program had an increase in their CSE during the counseling skill training course. Mullen, Uwamahoro, Blount, and Lambie () found that master’s‐level counseling students’ CSE increased over time as they progressed through the preparation program. However, although there are several studies that explored the development of students’ CSE, few studies exist to investigate a longitudinal change in students’ CSE throughout their preparation programs (e.g., from orientation to graduation from the program).…”
Section: Csementioning
confidence: 99%
“…They found statistically significant differences in CSE among ethnic groups but no significant differences by age and gender. Mullen et al () found no significant relationship between students’ cultural factors (i.e., age, gender, ethnicity, and program track) and their perceived CSE at each of their three data collection points in a longitudinal study on students’ CSE.…”
Section: Csementioning
confidence: 99%
“…The construct of self-efficacy has been researched in school counseling literature for a variety of topics (e.g., Bodenhorn & Skaggs, 2005;Bodenhorn, Wolfe, & Airen, 2010;Clark, 2006;Mullen, Uwamahoro, Blount, & Lambie, 2015;Owens, Bodenhorn, & Bryant, 2010;Scarborough & Culbreth, 2008;Woods, 2009). Woods (2009) identified that school counselors' (N = 980) length of experience correlated with increased self-efficacy.…”
Section: General Self-efficacy Ethical and Legal Self-efficacy And mentioning
confidence: 99%
“…These researchers indicated a moderate relationship between CSE and counseling performance measures, and that trainees with higher CSE may perceive their supervisory environments as being more positive and supportive. Additionally, multiple studies (e.g., Barbee, Scherer, & Combs, ; Cashwell & Dooley, ; Kozina, Grabovari, De Stefano, & Drapeau, ; Melchert, Hays, Wiljanen, & Kolocek, ; Mullen, Uwamahoro, Blount, & Lambie, ; Tang et al, ) have examined counseling trainee self‐efficacy.…”
Section: Self‐efficacymentioning
confidence: 99%